IMPACT OF MOISTURE DEPLETION PERCENTAGES ON SOME GROWTH CHARACTERS AND YIELD FOR SELECTED GENOTYPES OF BREAD WHEAT - & Baktash, Dhahi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
A field experiments were carried out at the Abu- Graib Research Station - Office of Agricultural Research  Ministry of Agriculture, to investigate moisture depletion  effect for some traits of selected genotypes during 2014-2015, which depended to the long term of breeding program (2008-2014). The 9th selected genotypes and the control variety IPA 99 were evaluated during season 2015-2016  using split plot arrangement within RCBD and three replications. The main plots included four levels of water stress (20%, 40%, 60% and 80%), depletion of available water while, genotypes occupied sub plots.The results revealed significant differences among depletion %, genotypes and their interaction in all studied characters. Moisture depletion 20%  of available water indicated the superiority of number days to 50% flowering (110.3 days), plant height (98..29 cm), flag leaf area (34.8 cm2), flag leaf angle  (67.700), number days to 100% physiological maturity (146.53 days), spike length (11.53 cm), number of spikelets spike-1 (18.07),  grain yield (5.06 t ha-1) and highest water use efficiency (1.63  kg m-3). The lowest value of the characters  were found by depletion 80% of available water. The genotype 179 to took highest number of days to 50% flowering (114 days), IPA99 had highest flag leaf area (33.21 cm2) and highest period of 100% physiological maturity (145.75 days), genotype 27 had highest plant height (102.11 cm) and 186 produced highest spike length (11.75 cm), highest number of spikelests spike-1 (19.58), highest yield  (5.64 t ha-1). Significant differences were found in interactions between genotypes and water stress in most characters studied, this shows of genotypes tolerance differences to water stress. So we can select one or more  genotype , which tolerance to 20% moisture depletion.